Serological Patterns of TORCH Infections in Early Pregnancy: Pola Serologis Infeksi TORCH pada Awal Kehamilan - Khzal, Alaa Mahdy Obaid (Academia Open, 2025)
General Background: TORCH infections—comprising Toxoplasma gondii, Rubella virus, Cytomegalovirus (CMV), and Herpes simplex virus (HSV)—pose severe risks to fetal health if acquired during pregnancy, particularly in the first trimester. Specific Background: In Iraq, and specifically Najaf, epidemiological data on TORCH prevalence among pregnant women remains scarce, despite the known perinatal risks. Knowledge Gap: The absence of localized seroprevalence data and gestational-age-based immunological profiles limits the development of targeted maternal-fetal health strategies. Aim: This study aimed to assess TORCH infection rates, identify immunoglobulin patterns (IgM and IgG), and compare seropositivity across pregnancy trimesters in Najaf. Results: Among 100 participants, 62% tested positive for TORCH infections, with 58.1% of those in the first trimester showing acute infections, mainly due to T. gondii and HSV. Later trimesters showed chronic infections dominated by CMV and Rubella, evidenced by IgG presence. Novelty: This is the first study in Najaf to report trimester-specific TORCH immunological dynamics, revealing a distinct shift from acute to chronic infection profiles. Implications: These findings highlight the necessity for early TORCH screening and ongoing antenatal surveillance in Iraq to minimize congenital complications and inform public health interventions. Highlight : Early Detection Critical – Most acute infections (58.1%) occur in the first trimester, requiring urgent screening and intervention. Pathogen Pattern Shifts – Toxoplasma and HSV dominate early infections, while CMV and Rubella persist chronically later. Public Health Need – Routine TORCH testing and hygiene education must be integrated into antenatal care programs. Keywords : TORCH Infections, Toxoplasma Gondii, Cytomegalovirus, Rubella Virus, Antenatal Screening